Impact of perinatal environmental tobacco smoke on the development of childhood allergic diseases - Hyeon-Jong Yang (Korean Pediatric Society, 2016)
Allergic diseases such as asthma, allergic rhinitis, atopic dermatitis, and food allergy, are most common chronic, noncommunicable diseases in childhood. In the past few decades, the prevalence has increased abruptly worldwide. There are 2 possible explanations for the rising prevalence of allergic diseases worldwide, that an increased disease-awareness of physician, patient, or caregivers, and an abrupt exposure to unknown hazards. Unfortunately, the underlying mechanisms remain largely unknown. Despite the continuing efforts worldwide, the etiologies and rising prevalence remain unclear. Thus, it is important to identify and control risk factors in the susceptible individual for the best prevention and management. Genetic susceptibility or environments may be a potential background for the development of allergic disease, however they alone cannot explain the rising prevalence worldwide. There is growing evidence that epigenetic change depends on the gene, environment, and their interactions, may induce a long-lasting altered gene expression and the consequent development of allergic diseases. In epigenetic mechanisms, environmental tobacco smoke (ETS) exposure during critical period (i.e., during pregnancy and early life) are considered as a potential cause of the development of childhood allergic diseases. However, the causal relationship is still unclear. This review aimed to highlight the impact of ETS exposure during the perinatal period on the development of childhood allergic diseases and to propose a future research direction.